Proposal of an instrument for the qualification, registration and certification of environmental consultants: Case study of Costa Rica - Quirós Vargas, Roberto (2017)
This research demonstrates that Costa Rica lacks of a standardized and systematized instrument for the qualification and registration of environmental consultants. The instrument is important to have the confidence and recognition of the Environmental Impacts Assessment by the Costa Rican civil society. This lack originates, among other issues, a variable quality of the Environmental Impact Assessments. As a methodology for the collection of data and other inputs of the study, Costa Rica legislation and ISO standards (i.e. ISO related to the accreditation and registration processes) were studied, and groups of experts (local and international) were interviewed to have inputs for the scheme. The main result of the research is the design of a qualification and registration scheme for the professionals who want to work as environmental consultants. The attributes included within the scheme to assess the work of environmental consultant were: education, experience, training and personal qualifications. These attributes were assessed for the two environmental consultants categories considered: EIA Coordinator and EIA Specialist.